Growrh, maturation and learning, thinking factors - Aguirre Chávez, Felipe (2018)
Know the potentialities of the categories, development, growth, maturation and learning, their nature, complexity and their relationship with biological and social factors, internal and external, maturation and growth as elements (of complementary opposites) unitary in the development of thought, much depends on what logic is assumed. In the present article, the analysis is approached from the interactive logic, open, evaluative, critical and its potential for development in the educational process and teaching-learning.